Identification of injuries and its prevention in physical education at elementary schools in Sukadana, Ciamis, West Java, 2020 - Fenima Brillianti Maudi; Hanik Liskustyawati; Djoko Nugroho (PHEDHERAL, 2020)
The main problem in identifying the injuries and its prevention in the Physical Education at elementary schools in Sukadana is the nescience of the level of the risk for injury and the injury management steps during the Physical Education subject. Some factors contributing on the nesciences are condition of facilities and infrastructure, school environmental conditions, student behavior and teacher’s conversance. Therefore, this research is purposed to determine the injuries that have occurred and the knowledge of teachers about injury management during Physical Education subject at elementary schools in Sukadana district. This research analyzes the injury management done by the Physical Education teachers at elementary schools in Sukadana district and the injuries that have occurred using some theories related to types and factors of injuries, as well as the proper steps of injury management. This research is a combination research model concurrent embedded (unbalanced mixture), namely a research method that combines qualitative methods and quantitative methods by mixing the two methods unequally. This research uses two kinds of data, primary and secondary data. The technique of collecting data in this research is saturation-sampling technique with the Physical Education teachers in Sukadana district as the informant. The validation of the data, collected from the result of questionnaire and passive participant observation, are then analyzed and tested using member check technique. The result of this research shows that teachers have significant role on diminishing the risk of injury and treating injured students during the Physical Education at the elementary schools in Sukadana district. Generally, the teachers have already had adequate conversance in treating wounded students. Moreover, the injuries occurred are dominated by minor injury. This is due to the learning materials that are still on the basic level. Furthermore, some moderate injuries are caused by student’s health condition, such as medical history and the fitness of the student, that is different one to another.